2013
DOI: 10.1021/jp3116319
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavenging by Natural Polyphenols: Atom versus Electron Transfer

Abstract: Polyphenols (synthetically modified or directly provided by human diet) scavenge free radicals by H-atom transfer and may thus decrease noxious effects due to oxidative stress. Free radical scavenging by polyphenols has been widely theoretically studied from the thermodynamic point of view whereas the kinetic point of view has been much less addressed. The present study describes kinetic-based structure-activity relationship for quercetin. This compound is very characteristic of the wide flavonoid subclass of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
117
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(121 citation statements)
references
References 72 publications
4
117
0
Order By: Relevance
“…In our earlier study we found that NOE exhibited a noticeable anti-inflammatory activity in several animal models of inflammation (17). Moreover, free radical scavenging properties of phenolic and flavonoid compounds were confirmed in some studies (37)(38)(39). In this study, phenolic and flavonoid contents of NOE detected to be 71 ± 6.23 gallic acid equivalents/g dried extract and 95.26 ± 7.6 mg rutin equivalents/g dried extract, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…In our earlier study we found that NOE exhibited a noticeable anti-inflammatory activity in several animal models of inflammation (17). Moreover, free radical scavenging properties of phenolic and flavonoid compounds were confirmed in some studies (37)(38)(39). In this study, phenolic and flavonoid contents of NOE detected to be 71 ± 6.23 gallic acid equivalents/g dried extract and 95.26 ± 7.6 mg rutin equivalents/g dried extract, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…After treatment with quercetin, the increased liver GSH level was reduced, which suggests that oxidative stress injuries were ameliorated. There are already existing reports that state that quercetin has a free radical scavenging activity (Pascoal et al, 2011;di Meo et al, 2013), so we can speculate that quercetin itself may have the capacity to scavenge free radicals, and thus substitute for the function of GSH, which leads to a decrease of GSH levels in quercetin-treated mice.…”
Section: Discussionmentioning
confidence: 70%
“…S9) (Di Meo et al, 2013;Litwinienko & Ingold, 2007). In addition to being influenced by the properties of the reactants, the relative contribution of each mechanism to the overall process is highly dependent on the ability of the solvent to promote ionisation of the phenol and to accept hydrogen bonds (HBs) (Litwinienko & Ingold, 2007).…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…In addition to being influenced by the properties of the reactants, the relative contribution of each mechanism to the overall process is highly dependent on the ability of the solvent to promote ionisation of the phenol and to accept hydrogen bonds (HBs) (Litwinienko & Ingold, 2007). The rate constant for electron transfer (k ET ) (the rate limiting step of SPLET (Di Meo et al, 2013)) is normally much greater than the rate constant for HAT (k HAT ), hence SPLET can be the prevailing mechanism even at very low phenoxide concentrations (Litwinienko & Ingold, 2007). In solvents with high dielectric constants and good anion solvation abilities (e.g.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%